2019
DOI: 10.1016/j.nicl.2019.101951
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant regional homogeneity in post-traumatic stress disorder after traffic accident: A resting-state functional MRI study

Abstract: Objectives The present study explored the changes in spontaneous regional activity in post-traumatic stress disorder (PTSD) patients, who experienced severe traffic accidents. Methods 20 drug-naive PTSD patients and 18 healthy control subjects were imaged using resting-state functional magnetic resonance imaging (rs-fMRI) and analyzed by the algorithm of regional homogeneity (ReHo). Results Compared to the healthy control group, the PTSD grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Stronger connectivity with the medial temporal lobe was shown during recovery of information, when compared to the left angular gyrus 88 . Previous studies have explored regional spontaneous brain activity (called regional homogeneity, or ReHo) changes in PTSD patients who suffered severe traffic accidents 89 . Relative to controls, participants with PTSD showed weaker right angular gyrus ReHo, and a negative correlation of right angular gyrus with CAPS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger connectivity with the medial temporal lobe was shown during recovery of information, when compared to the left angular gyrus 88 . Previous studies have explored regional spontaneous brain activity (called regional homogeneity, or ReHo) changes in PTSD patients who suffered severe traffic accidents 89 . Relative to controls, participants with PTSD showed weaker right angular gyrus ReHo, and a negative correlation of right angular gyrus with CAPS scores.…”
Section: Discussionmentioning
confidence: 99%
“… Zhan et al (2016) reported that reduced spontaneous neural activity in acute mTBI patients might be linked with emotional and cognitive disorders ( Zhan et al, 2016 ). fALFF and ReHo are common analytical methods used for investigating the pathophysiology of various neuropsychological disorders ( Zhan et al, 2015 ; Yang et al, 2018 ; Fu et al, 2019 ; Wang et al, 2019 ; Che et al, 2020 ; Mo et al, 2020 ). In this study, we took advantage of these tools to explore the neurological mechanism of chronic mTBI and its relationship with cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…They also have found a negative correlation between decreased ReHo values in the right AG and symptom severity of PTSD (CAPS). The researchers concluded that ReHo alteration in the AG is a common feature of PTSD that could be associated with dissociative symptoms of PTSD ( Fu et al, 2019 ). The results of our study are consistent with this conclusion, as we have observed increased ReHo values in the right AG that were negatively associated with clinical scores including RPQ-13 and trail making A.…”
Section: Discussionmentioning
confidence: 99%
“…The second method was an FDR correction ( p < 0.05) [ 50 , 51 ]. The third strategy was a PT containing 5000 permutations with TFCE, which has been reported to reach the optimal balance between family-wise error rate (< 5%) and test-retest reliability and showed optimal results in recent fMRI studies [ 20 , 52 , 53 ]. Age was also included as a covariate factor in the statistical analysis, with a previous study indicating an association between age and functional activity [ 54 ].…”
Section: Methodsmentioning
confidence: 99%